Walking and cycling, as active transportation, and obesity factors in adolescents from eight countries - Ferrari, Gerson Luis de Moraes (2022)
Background: Evidence has shown that active transportation decreases obesity rates, but considering walking or cycling as separate modes could provide additional information on the health benefts in adolescents. This study aimed to examine the associations between walking and cycling as form active transportation and obesity indicators in Latin American adolescents. Methods: Population-based study with 671 adolescents (mean age: 15.9 [standard deviation: 0.8] years) from eight countries participating in the Latin American Study of Nutrition and Health/Estudio Latino Americano Nutrition y Salud (ELANS). Walking and cycling for active transportation were measured using the International Physical Activity Ques‑ tionnaire long version. Body mass index, waist circumference, neck circumference, and relative fat mass were used as obesity indicators. Associations were estimated using logistic regression models for the pooled data adjusted for country, sex, age, socio-economic levels, race/ethnicity, leisure-time physical activity and energy intake. Results: Mean time spent walking and cycling was 22.6 (SD: 33.1) and 5.1 (SD: 24.1) min/day, respectively. The median values were 12.8 (IQR: 4.2; 25.7) and 0 (IQR: 0; 6.2) for walking and cycling. Participants reporting≥10 min/ week of walking or cycling for active transportation were 84.2% and 15.5%, respectively. Costa Rica (94.3% and 28.6%) showed the highest prevalence for walking and cycling, respectively, while Venezuela (68.3% and 2.4%) showed the lowest prevalence. There was no signifcant association between walking for active transportation and any obesity indicator. In the overall sample, cycling for≥10 min/week was signifcantly associated with a lower likelihood of overweight/obesity based on BMI (OR: 0.86; 95%CI: 0.88; 0.94) and waist circumference (OR: 0.90; 95%CI: 0.83; 0.97) adjusted for country, sex, age, socio-economic level, race/ethnicity, leisure-time physical activity and energy intake compared to cycling for<10 min/week. There were no signifcant associations between cycling for active transporta‑ tion and neck circumference as well as relative fat mass.